Berberine improves glucogenesis and lipid metabolism in nonalcoholic fatty liver disease - Zhao, Li (BMC Endocr Disord, 2017)
BACKGROUND: Nonalcoholic fatty liver disease (NAFLD) is considered a critical hepatic manifestation of metabolic syndrome. Berberine (BBR) exerts anti-hyperglycemic and anti-dyslipidemic effects and can also ameliorate NAFLD. Thus, BBR might exert its therapeutic effect on NAFLD by improving glucolipid metabolism. Here, we investigated the aspects and extent to which glucolipid metabolism were affected by BBR in rats with NAFLD. METHODS: Three groups of Sprague–Dawley rats were studied: a control group (n = 6) fed a normal chow diet and a NAFLD group (n = 6) and a NAFLD + BBR group (n = 6) fed a high-fat diet. Normal saline and BBR (150 mg/kg body weight/day for 16 weeks) were administered by gavage. All rats were infused with isotope tracers. The rates of glucose appearance (Ra(glu)), gluconeogenesis (GNG) and glycerol appearance (Ra(gly)) were assessed with (2)H and (13)C tracers, whereas the rates of hepatic lipogenesis and fatty acid β oxidation were measured using the (3)H tracer. RESULTS: When the NAFLD model was successfully induced by administering a high-fat diet, body weight, insulin resistance and dyslipidemia were significantly increased. After the BBR treatment, weight loss, decreased lipid profiles and HOMA-IR, and increased ISI were observed. Meanwhile, BBR reduced Ra(glu), GNG and hepatic lipogenesis, whereas the rate of fatty acid β oxidation in skeletal muscle showed an increasing trend. Ra(gly) showed a decreasing trend. Based on the results of the histological analysis, BBR obviously attenuated the ectopic liver fat accumulation. CONCLUSIONS: BBR improved NAFLD by inhibiting glucogenesis and comprehensively regulating lipid metabolism, and its effect on inhibiting hepatic lipogenesis was much stronger. The improvement may be partly mediated by weight loss. Berberine might be a good choice for patients with NAFLD and glucose metabolic disorder. Future clinical trials need to be conducted to confirm these effects.